Novel Gemini vitamin D3 analogs: Large structure/function analysis and ability to induce antimicrobial peptide. Issue 1 (16th July 2013) - Okamoto, Ryoko; Gery, Sigal; Kuwayama, Yoshio; Borregaard, Niels; Ho, Quoc; Alvarez, Rocio; Akagi, Tadayuki; Liu, George Y.; Uskokovic, Milan R.; Koeffler, H. Phillip
<x xml:space="preserve">Abstract</x> We have synthesized 39 1, 25‐dihydroxyvitamin D3 [1, 25(OH)2D3] analogs having two side chains attached to carbon‐20 (Gemini) with various modifications and compared their anticancer activities. Five structure–function rules emerged to identify analogs with enhanced anticancer activity. One of these active analogs, BXL‐01‐0126, was more potent than 1, 25(OH)2D3 in mediating 50% clonal inhibition of cancer cell growth. Murine studies found that BXL‐01‐0126 and 1, 25(OH)2D3 had nearly the same potency to raise serum calcium levels. Taken together, BXL‐01‐0126 when compared to 1, 25(OH)2D3 has greater anticancer potency, but similar toxicity causing hypercalcemia. We focused on the effect of these compounds on the stimulation of expression of human cathelicidin antimicrobial peptide (CAMP) whose gene has a vitamin D response element in its promoter. Expression of CAMP mRNA and protein increased in a dose‐response fashion after exposure of acute myeloid leukemia (AML) cells to the Gemini analog, BXL‐01‐126, in vitro. A xenograft model of AML was developed using U937 AML cells injected into NSG‐immunodeficient mice. Administration of vitamin D3 compounds to these mice resulted in substantial levels of CAMP in the systemic circulation. This suggests a unique prophylactic treatment at diagnosis or during induction chemotherapy for AML patients to provide them with protection against various microbial infections through CAMP induction.